2020
DOI: 10.3390/pharmaceutics12111039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyaluronic Acid and Pluronic-F68 on the Surface Properties of Foam as a Delivery System for Polidocanol in Sclerotherapy

Abstract: The use of foams to deliver bioactive agents and drugs is increasing in pharmaceutics. One example is the use of foam as a delivery system for polidocanol (POL) in sclerotherapy, with the addition of bioactive compounds to improve the delivery system being a current subject of study. This work shows the influence of two bioactive additives on the structure and stability of POL foam: hyaluronic acid (HA) and Pluronic-F68 (F68). HA is a natural non-surface-active biopolymer present in the extracellular matrix wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For instance, modified foam sclerosants are formed by adding other surfactants to prolong the half-life of the foam. Injectable in situ gels are available to be applied directly at the lesion site to control drugs released locally and avoid many adverse reactions [11,12]. Traditional polymer gels with covalent bonds are commonly used but difficult to degrade in vivo [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, modified foam sclerosants are formed by adding other surfactants to prolong the half-life of the foam. Injectable in situ gels are available to be applied directly at the lesion site to control drugs released locally and avoid many adverse reactions [11,12]. Traditional polymer gels with covalent bonds are commonly used but difficult to degrade in vivo [13].…”
Section: Introductionmentioning
confidence: 99%
“…The equation predicts a linear relationship between foam stability and viscosity, all other factors being constant. Moreover, a recent study from Castillo 23 indicated that HA increased the surface viscoelasticity of POL, which had a positive impact on the stability of foam. More HA in POL signifies more viscous, cohesive, and stable foam.…”
Section: Discussionmentioning
confidence: 96%
“…One unique application of foam delivery is sclerotherapy. Nonetheless, these sclerotherapeutic injections were performed in a very limited area, and a low volume of foam was applied [ 26 ].…”
Section: Discussionmentioning
confidence: 99%